Long-Term Projections of Patients Undertaking Renal Replacement Therapy Under the Universal Coverage Scheme in Thailand - Thammatacharee N; Suphanchaimat R (Dove Medical Press, 2020)
Noppakun Thammatacharee, 1, 2 Rapeepong Suphanchaimat 2, 3 1Health Systems Research Institute, Nonthaburi, Thailand; 2International Health Policy Program (IHPP), the Ministry of Public Health, Nonthaburi, Thailand; 3Division of Epidemiology, Department of Disease Control, The Ministry of Public Health, Nonthaburi, ThailandCorrespondence: Noppakun ThammatachareeHealth Systems Research Institute, 4th Floor, National Health Building, 88/39 Tiwanon 14 Road, Taradkwan, Muang District, Nonthaburi 11000, ThailandTel +66 2832 9212Fax +66 2832 9202Email noppakun@hsri.or.thIntroduction: The increasing number of patients with end-stage renal disease and the cost of their treatment may potentially place a large burden on overall healthcare spending and human resources for health. We projected the number of patients with end-stage renal disease to better estimate arrangements needed in the future.Materials and Methods: We used a dataset containing information about patients who registered with the three modalities of the renal replacement therapy (RRT) program from 2009 to 2017: continuous automated peritoneal dialysis (CAPD), hemodialysis (HD) and kidney transplant (KT). An autoregressive integrated moving average model was used to predict the number of patients who would enroll in the RRT program from 2018 to 2027.Results: From 2009 to 2017, there was a constant increase in the volume of CAPD patients, although a slight drop in some periods was observed. HD patients outnumbered CAPD patients during the inception period of the program. After mid-2013, the trend in HD patients accelerated to the same pace as CAPD patients. By the end of 2017, the number of patients increased to 20,000 for CAPD and 15,000 for HD. The number of KT patients was extremely small relative to CAPD and HD patients. The program enrolled patients receiving a kidney transplant at a constant rate of approximately 200 per year after 2013. The predicted numbers of patients on RRT corresponded to an annual growth rate of 7.2– 7.4% for CAPD and HD and 4.8% for KT.Conclusion: Despite the expected increased volume of patients, the year-by-year growth rate of patients in all RRT modalities seemed to diminish over time. This phenomenon is likely explained by the intensive implementation of policies to address risk factors of non-communicable diseases among Universal Coverage Scheme (UCS) beneficiaries.Keywords: dialysis, kidney transplant, universal health coverage, ARIMA